Assessment of metatextual consciousness and its prediction of reading comprehension - Cunha, Neide de Brito (2019)
This study aimed to reveal evidence of the validity of the Assessment Questionnaire of Metatextual Awareness (QACM). The main objective was to verify whether metatextual awareness could predict reading comprehension, and the secondary objectives were: to verify metatextual awareness and reading comprehension through two Cloze tests and the QACM; to search criterion validity evidence based on the variable “school year”; and to identify the internal consistency index of the items. The participants were 277 elementary school students from a public school in the state of São Paulo. The results showed that the students’ average scores increased from the 3rd to the 5th years ofschool, demonstrating a criterion validity of the school year. The QACM got a good internal consistency index of 0.80. The performance on the QACM explains 46% of the performance variance on the Cloze, showing that they are shared skills. Keywords: metatextual awareness; reading comprehension; elementary school;  Cloze; validity.